Neutron noise control techniques for VVER core - Arkadov, G. V.; Slepov, M. T. (Глобальная ядерная безопасность, 2024)
Many research staffs and groups have paid considerable attention to the issues of noise analysis and control of nuclear power plant operation parameters. This is reflected in the scientific environment in the form of numerous publications, monographs, articles, and reviews devoted to the study of noise components of various variation signals of reactor plants. However, despite the advanced theoretical works on this topic, applied research, i.e. direct reactor experiments, remains aside from the interests of both local and foreign scientists. The need of practical research is due to the complexity of interpretation of a variety of anomalies detected by noise methods, as well as the need to fine-tune various models. In addition, the spectral images of equipment can differ significantly not only between different designs of reactor plants, but also within the same-type units at one NPP. These problems cannot be solved by theoretical or computational methods alone, or by using simulation modeling. The situation is complicated by the fact that noise studies are a complex task both in terms of selecting noise data sources and interpreting the obtained information. Probably, these reasons explain the significant decrease of interest to experimental works on noise subject at various reactor plants both in the world practice and in Russia. The paper briefly discusses some possibilities of methods of neutron-noise control of cores aimed at improving the reliability and safety of NPPs. In addition, the article considers ways to reduce the labor intensity of their use for the earliest possible detection of anomalous condition of various equipment.